(untitled) (Proceedings of the World Disability & Rehabilitation Conference, 2019)
The relevance of the latent deviance problem is associated with the acute need to explain the psychological content of socialization disorders in pre-adolescence. The large number of age-related problems of pre-school and primary school age in particular determines the variety of specific configurations of the failure of the child in solving these problems at every stage of development. Polymorphism of the clinical disontogenesis also contributes to this variability. This situation necessitates the search for integrative structures, reflecting the emerging failure of the preschool and primary school children with disabilities, and the risks of further violations of socialization and development of deviations. The phenomenon of latent deviance, acting as a premorbid for deviations can be considered as an integrative formation. In the study of psychological content of latent deviance is of great importance the anticipatory competence study, which is considered a significant indicator of deviations in adolescents and adults. The study of anticipation in children with certain types of developmental disorders suggests its